Ethnic Diversities as Development Capital in Southeast Asia Region - Aryowiloto, Julang (Global Local Interactions: Journal of International Relations, 2019)
Each country development policy in Southeast Asia region still prefer to economics dimension orientation. However, social and cultural considerations are also important in development policy, such as ethnic diversities. Southeast Asia as a region full of ethnic diversities needs to utilize this advantage as a capital in order to region development. This paper addressed to analyse the importance of ethnic diversities as consideration of development policy in Southeast Asia region. At first, by elaborate development approach which socio cultural oriented especially ethnicity namely ethnodevelopment include its criticisms. Then, this paper elaborates about the ethnic diversities in Southeast Asia and how much its potential can utilize as region development capital. Finally, this paper provides a conclusion that every single policy maker in every country around Southeast Asia strongly need to concern and consider ethnic diversities start from process until implementation of the development policy which end up to dynamic equilibrium and advancement of Southeast Asia region development.